English for Accounting as a Learning Tool for Students with Different Mother Tongue - Miftahul Jannah; Nabila Nur Azizah; Abdul Syahid (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This research explored the role of English for Accounting as a learning tool for students with different mother tongues, focusing on its effectiveness in enhancing comprehension of accounting terminology and supporting technical skill development. Using a qualitative approach, insights were gathered from interviews and document analysis with fifth-semester accounting students to evaluate the book's accessibility and the challenges faced due to language barriers. Findings suggested that while the book was generally effective in introducing accounting concepts, additional support from knowledgeable instructors was crucial for deeper understanding. Recommendations for improving language accessibility were also discussed.